The development of a scale to measure psychological skills for judo players - Yamamoto, K.; Shimamoto, K.; Nagaki, K. (Research Journal of Budo, 2015)
The purpose of this study was to develop a scale evaluating the psychological skills for judo players (PSJP). In a preliminary study during summer 2013, a questionnaire consisting of 60 items to evaluate the PSJP was developed based on the twelve subscales of "Diagnostic Inventory of Psychological Ability for Athletes" (Tokunaga and Hashimoto, 2000). In the main study during fall 2013, an exploratory factor analysis (principal factor method, promax rotation) was conducted using the questionnaire data obtained from 369 Judo players (junior high school = 95, high school = 90, college = 89, adult = 95). The reliability and validity of the scale were estimated by Cronbach`s alpha coefficient and construct validity, respectively. The exploratory factor analysis revealed that the scale had four subscales: tactical thinking ability, practice desire, receptivity of others, and support of others. Each subscale showed satisfactory reliability coefficients. In addition, significant correlations were observed between each subscale overall scale in order to verify construct validity. Results of covariance structure analysis showed that the factor analysis model of PSJP fitted the data moderately (GFI = .88, AGFI = .85, CFI = .91, RMSEA = .07). Then, the relationship between PSJP and the competitive results of participants were compared using the scale. Participants with high competitive results had significantly higher scores on tactical thinking ability, practice desire and support of others than participants with low competitive results. Consequently, the developed scale PSJP appeared moderately reliable and valid.